Management of Scientific Experiments in Computational Modeling: Challenges and Perspectives - Braga, Regina Maciel (2012)
Currently the computer is essential to the success in conducting scientific research. In this context, e-Science appears as science performed with computer support aiming efficiency. The challenge, “Computational Modeling of artificial, naturals and socio-cultural complex systems and man-nature interaction” from SBC Great Challenges is strongly related to the e-Science context. The goal of this challenge is to create, evaluate, modify, compose, manage and exploit computer models in fields related to complex, artificial, natural, socio-cultural and human-nature systems. Technologies like semantic web service composition, data provenance, peer to peer networks and scientific software product line can be used as basis for the specification and development of an e-Science infrastructure to handle challenges and solve problems. This paper discusses the main challenges involved in developing an eScience infrastructure, presenting research challenges for the next years.